M4 Meeting the psychological needs of copd patients and enhancing self-efficacy: integrating clinical psychology in a community respiratory service. (15th November 2017) - Chan, CSJ; Graham, L; Roots, D; Hodson, M; Sunak, S
Abstract : Introduction and Objectives: An average of 40% of Chronic Obstructive Pulmonary Disease (COPD) patients suffer from clinical depression and anxiety disorders, at least twice as much as reported by the general population. In COPD patients, comorbid mental health problems significantly predict more frequent symptom exacerbation, inpatient admissions, poorer functional status and quality of life due to reduced self-care. Typically up to 50% of treated COPD patients reported improvements of depression and anxiety symptoms after psychological therapy. However, conventional mental health services (e.g., Improving Access to Psychological Therapies services) have experienced challenges in engaging, assessing, and treating this patient group. The current study explores the clinical outcomes of a psychology service integrated into the existing COPD management frameworks and pulmonary rehabilitation programs in the London Borough of City and Hackney; in particular its impact on patients' access to psychological therapy, changes in mental health symptoms, quality of life and patient experiences of COPD. Methods: Self-reported experience of mental health symptoms was measured by the Hospital Anxiety and Depression Scale (HADS). Changes in patient experiences' including their perceived control and adjustment pre- and post-psychological interventions was measured by the COPD Patients-reported Experience Measure (COPD-PREM9). Results: In the 12 months between April 2016 and March 2017, the integrated psychology service received referral for 122 and offered interventions for 108 COPD patients, a significant improvement from that reported by the local IAPT service. 52 out of 108 patients who completed treatment required home-based psychological interventions due to their physical needs and were unsuitable for IAPT services. 44% reported a significant improvement in their symptoms of anxiety and 38% with depression, comparable to the average recovery rate (41.6%) of physically healthy patients in London IAPT services during the same period. Overall 80% of patients showed significant improvement in their experience of their COPD, including their perceived control and adjustment to the condition. Conclusions: An integrated clinical psychology service offers significant advantage to traditional mental health services in improving service access, symptoms reduction, and improvement in self-reported quality of life of COPD patients.